Solar energy driven photocatalytic membrane modules for water reuse in agricultural and food industries. Pre-industrial experience using s-triazines as model molecules - Ignazio Renato Bellobono; Franca Morazzoni; Riccardo Bianchi; Emilia Simona Mangone; Rodica Stanescu; Cristina Costache; Paola Maria Tozzi (International Journal of Photoenergy)
A membrane module, utilizing photocatalytic membranes, has been employed in a pilot plant, in conditions of solar irradiation, to investigate photomineralisation of atrazine, propazine, terbutylazine, symazine, prometryn, and ametryn, as model molecules of s-triazine herbicides, at a standard concentration (1.0 ppm) simulating those of contaminated aquifers, by using ozone as oxygen supplier. Photocatalytic composite membranes immobilised 30±3 wt.% of TiO2 and 6 wt.% of a synergic mixture of tri-(t-butyl)- and tri-(i-propyl)vanadate(V). Photomineralisation was followed by analysis of substrate disappearance, as such, and by total organic carbon (TOC) analysis. A four parameters kinetic model was employed, as set up in previous studies of this series, to interpret the whole photomineralisation curve. Quantum yields, as indicative of catalytic and photocatalytic mechanisms, were evaluated satisfactorily: they are discussed, and compared with those of previous studies on the same substrates, carried out in the same module, but in conditions of practically monochromatic irradiation (254 nm) within the range of optical absorption of semiconductor. Finally, in order to compare effectiveness of composite photocatalytic membranes, described above, prepared by photografting, either in the presence or in the absence of an added photopromoter, as well as that of metallic membranes, onto which the semiconductor without any photopromoter was present as a 3–4 μm thick surface layer, directly produced on the nanotechnologically treated surface, with those of other commercial materials, parallel experiments were carried out, by using commercial sheets in which the semiconductor was immobilised, by a method based substantially on glueing by colloidal silica. All of these comparison experiments were carried out at a laboratory scale, by using, in these experiments, dioxygen of air, or ozone as oxygen donors.